(untitled) (Nativa, 2019)
A demanda crescente por alimentos, associada à necessidade de preservação ambiental, e a disponibilidade limitada de terras para a expansão da área cultivada, tem demandado desenvolvimento contínuo de tecnologias que resultem no aumento da produtividade de grãos, na racionalização do uso de insumos, dos recursos ambientais e dos meios de produção. O presente trabalho teve como objetivo avaliar o desempenho da soja (Glycine max (L.) Merrill) semeada em sucessão ao consórcio de milho (Zea mays L.) segunda safra com diferentes densidades de Crotalaria spectabilis. O experimento foi semeado em 15 de fevereiro de 2016, em uma área experimental da Embrapa Agrossilvipastoril, na cidade de Sinop/MT. O delineamento utilizado foi de blocos ao acaso, com quatro repetições. Cada parcela apresentava 11 linhas com 0,45 cm de espaçamento entre si e 10 metros de comprimento, sendo considerada, como área útil, as três linhas centrais. Os tratamentos foram constituídos de 4 densidades da C. spectabilis, sendo 10, 20, 30 e 40 kg de sementes por ha, além da testemunha, com milho solteiro. A semeadura da soja foi realizada em outubro de 2016, sob as parcelas colhidas do consórcio de milho com crotalária. Ao final do ciclo, coletou-se 10 plantas da área útil de cada parcela, para que fossem avaliados os componentes de produção e produtividade da cultura. Observou-se que a crotalária não causou redução na produtividade de grãos do milho, porém em apenas um ciclo de consórcio, não permitiu que se obtivessem incrementos na produtividade de grãos da soja. Palavras-chave: diversificação de culturas; consórcio milho-crotalária; produtividade de grãos. PERFORMANCE OF SOYBEAN IN SUCCESSION TO MAIZE SECOND CROP INTERCROPPED WITH DIFFERENT SOWING DENSITY WITH Crotalaria spectabilis ABSTRACT: The growing demand for food, associated with the need for environmental preservation, and the limited availability of land for the expansion of cultivated area, has demanded continuous development of technologies that result in increased grain productivity, rationalization of input use, environment resources and the means of production. The objective of this work was to evaluate the performance of soybean (Glycine max (L.) Merrill) in succession to the intercropped of maize (Zea mays) second crop with different densities of Crotalaria spectabilis. The experiment was sowing on February 15, 2016, in an experimental area of Embrapa Agrossilvopastoral, in the city of Sinop/MT. The experimental design was a randomized complete block, with four replications. Each plot had 11 lines with 0.45 cm of spacing and 10 meters of length, being considered as useful area, the three central plots. The treatments consisted of 4 densities of C. spectabilis, being 10, 20, 30 and 40kg of seeds per hectare, besides the control with the single maize. The sowing of the soybean was carried out in October 2016, under the plots harvested from the maize intercropped with the Crotalaria, where the cultivar M 8210IPRO was used and at the end of the cycle 10 plants of the useful area of each plot were collected, so that Production components. With the results obtained, it was possible to observe that the crotalaria did not cause a reduction in corn grain yield, but in only one consortium cycle, it did not allow the increase of grain yield of the soybean. Therefore, the continuity of the work must be carried out in order to be able to obtain increases in soybean production in succession, and also to evaluate the best C. spectabilis density to be used in intercropping. Keywords: crop diversification; maize-crotalaria intercrop; grain yield.